Platform for energy generation based on piezoelectric elements - Peter Adel Wakеm Awad; Anastasia A. Sidorova; Tatyana E. Mamonova (Известия Томского политехнического университета: Промышленная кибернетика, 2023)
In recent decades, we have seen rapid advances in science and technology in renewable and alternative energy. In this context, the research related to energy generation from non-obvious sources is becoming increasingly relevant. Particular attention is paid to the ability of energy extracting from everyday human activities such as walking. The use of piezoelectric elements (AC_alternating current DC_direct current) is one of the promising approaches to achieving this goal. The device presented in the work is capable of converting mechanical deformation, for example from the pressure of a person stepping on a platform, into electrical energy. The idea of generating energy through piezoelectric elements when walking represents an innovative approach for use in everyday devices. When a person moves, his steps have a mechanical effect on the surface under his feet. This process can be captured using built-in piezoelectric elements that turn each step into an electrical impulse. If there are a sufficient number of piezoelectric elements and optimal organization, a significant amount of energy can be obtained. The aim of the presented work is to develop and study the hardware and software part of the platform for energy generation based on piezoelectric elements.